2011
DOI: 10.1007/s11302-011-9236-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P2Y receptors in the rat anterior pituitary

Abstract: In this study, the distribution patterns of P2Y 1 , P2Y 2 P2Y 4 , P2Y 6 , P2Y 12 , and P2Y 13 receptors in the anterior pituitary cells of rat were studied with doublelabeling immunofluorescence and Western blot. The results showed that P2Y receptors were widely expressed in the anterior pituitary. P2Y 1 and P2Y 4 receptors were found to be expressed in the majority of gonadotrophs and thyrotrophs, P2Y 2 receptors were expressed in a small subpopulation of lactotrophs and almost all the folliculo-stellate cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
4
7
0
Order By: Relevance
“…Earlier studies with dispersed pituitary cells revealed the presence of this type of receptors in lactotrophs and other non-identified cell type [36]. Immunoreactive P2Y1 receptors were identified in rat thyrotrophs [37] and our experiments shows that mouse TαT1 cells also express functional P2Y1 receptors. In contrast to TRH-responsive lactotrophs, which express P2X4 receptor channels as well [38], the present data suggest that P2X receptor channels capable of generating global calcium signaling are not expressed in TαT1 cells.…”
Section: Discussionsupporting
confidence: 68%
“…Earlier studies with dispersed pituitary cells revealed the presence of this type of receptors in lactotrophs and other non-identified cell type [36]. Immunoreactive P2Y1 receptors were identified in rat thyrotrophs [37] and our experiments shows that mouse TαT1 cells also express functional P2Y1 receptors. In contrast to TRH-responsive lactotrophs, which express P2X4 receptor channels as well [38], the present data suggest that P2X receptor channels capable of generating global calcium signaling are not expressed in TαT1 cells.…”
Section: Discussionsupporting
confidence: 68%
“…In human thyrotrophs, ATP stimulates the calcium-phosphatidylinositol cascade, indicating the presence of P2YRs (Raspe et al, 1991). Consistent with these findings, an immunohistochemical study has shown that the majority of rat pituitary thyrotrophs express P2Y1 and P2Y4R (Yu et al, 2011). In addition, pharmacological evidence points to the presence of A 1 R and A 2a R in thyrotrophs.…”
Section: Purinergic Regulation Of the Hypothalamic-pituitary-thyrosupporting
confidence: 54%
“…Immunohistochemical analysis suggested that P2Y 1 R and P2Y 4 R are expressed in gonadotrophs (Yu et al, 2011) and single cell calcium analysis proposed the expression of P2Y 2 R in these cells (Chen et al, 1995; Chen et al, 1996a; Chen et al, 1996b; Chen et al, 1994). However, electrophysiological analysis in gonadotrophs from embryonic, neonatal, and adult rats revealed that ATP application generates a depolarizing and non-oscillatory current, in contrast to calcium-mobilizing GnRH that triggered an oscillatory hyperpolarizing current driven by small calcium-controlled potassium channels (Stojilkovic et al, 2010b).…”
Section: Purinergic Regulation Of the Hypothalamic-pituitary-gonadmentioning
confidence: 99%
“…Of the remaining two tested antibodies, the Santa Cruz reagent was used with seemingly good results in mouse skeletal muscle (Chen et al, 2011) and in rat anterior pituitary (Yu et al, 2011a) and for the MBL antibody we could not find specific references of its use, but Jiang et al demonstrated apparently specific staining with an antibody made to the same epitope (Jiang et al, 2009). …”
Section: Discussionmentioning
confidence: 99%